A novel and efficient approach to obtain lignin-based polyols with potential industrial applications. Issue 46 (4th November 2020) - Perez-Arce, Jonatan; Centeno-Pedrazo, Ander; Labidi, Jalel; Ochoa-Gómez, José R.; Garcia-Suarez, Eduardo J.
Abstract : Current work is paving the way to manufacture, by new benign route, lignin-based polyols families with application in biopolymers synthesis. Abstract : A family of lignin-based polyols (LBPs) has been prepared and characterized using a novel and unprecedented synthetic approach consisting of a cationic ring opening polymerization reaction of oxiranes in the presence of tetrahydrofuran as both the solvent and co-monomer and an organosolv lignin (OL) at atmospheric pressure and room temperature in acidic media. This new route avoids the drawbacks of the current base-catalyzed lignin oxypropylation method used to obtain LBPs, such as the formation of a large amount of side products, the harsh reaction conditions (high temperatures (>150 °C) and pressure) resulting in lignin fragmentation and the generation of phenolic moieties that produce an unpleasant odour limiting the fields of application of LBPs. To demonstrate the versatility of the novel proposed synthetic route, several LBPs were obtained using butylene oxide, propylene oxide, glycidol and epichlorohydrin as oxiranes. The characterization of the obtained LBPs was performed by means of gel permeation chromatography (GPC), thermo-gravimetric analysis (TGA), differential scanning calorimetry (DSC), and attenuated total reflection-Fourier transform infrared (ATR-FTIR), as well as determination of the hydroxyl number. LBPs with a lignin content from 11.3 to 30.1 wt%, and weight average molecular weights from 2730 to 30 258 g mol −1, and hydroxyl values from 53 to 253 mg KOH per g were obtained. Furthermore, the reactivity of these LBPs with diisocyanates was evidenced and a plausible reaction mechanism is proposed. This novel developed method is of potential industrial interest, mainly in the field of the pulp industry, of which the major byproduct is lignin, as well as in the bio-polyol and bio-polymer industries.